2011 IEEE Vehicle Power and Propulsion Conference 2011
DOI: 10.1109/vppc.2011.6043192
|View full text |Cite
|
Sign up to set email alerts
|

An automotive on-board 3.3 kW battery charger for PHEV application

Abstract: An on-board charger is responsible for charging the battery pack in a plug-in hybrid electric vehicle (PHEV). In this paper, a 3.3kW two stage battery charger design is presented for a PHEV application. The objective of the design is to achieve high efficiency, which is critical to minimize the charger size, charging time and the amount and cost of electricity drawn from the utility. The operation of the charger power converter configuration is provided in addition to a detailed design procedure. The mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(42 citation statements)
references
References 9 publications
0
42
0
Order By: Relevance
“…However, the potential applications of a single phase twoswitch buck type AC-DC Converter topology with inductor voltage control appears to be a good candidate for high current battery charging applications, when used as a PFC converter due to the fact that the CC and CV type battery charging characteristics can be easily implemented [18]. A variety of circuit topologies, and control methods have been developed for PEV battery chargers [15,[19][20][21][22][23][24][25]. Single-stage AC-DC power conversion where the low frequency ripple is large in the output current is only suitable for lead acid batteries.…”
Section: On-board Battery Chargers Their Design Philosophy and Mmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential applications of a single phase twoswitch buck type AC-DC Converter topology with inductor voltage control appears to be a good candidate for high current battery charging applications, when used as a PFC converter due to the fact that the CC and CV type battery charging characteristics can be easily implemented [18]. A variety of circuit topologies, and control methods have been developed for PEV battery chargers [15,[19][20][21][22][23][24][25]. Single-stage AC-DC power conversion where the low frequency ripple is large in the output current is only suitable for lead acid batteries.…”
Section: On-board Battery Chargers Their Design Philosophy and Mmentioning
confidence: 99%
“…Therefore, this topology is good for power range below 1 kW [15,23]. Significant study outcomes related to single phase charger models are given in [15][16][17][18][19][20][21][22][23][24][25]. Based on a wide ranging study of literature it has been found that flyback converter operating in discontinuous current mode is the preferred topology [22].…”
Section: On-board Battery Chargers Their Design Philosophy and Mmentioning
confidence: 99%
“…Mode 4(t 3 <t<t 4 ): This mode begins when Q f is switched on. The primary current freewheels through Q 1 and Q 3 . The transformer primary current during this mode is given by:…”
Section: Converter Description and Operation Principlementioning
confidence: 99%
“…Full-bridge converters with a high power density and high efficiency have been proposed and used in many industry products such as server power units [1], telecommunication power units [2], and electric vehicle (EV) and plug-in hybrid electric vehicle (PHEV) battery chargers [3], [4]. Single-phase power factor correction (PFC) is normally adopted in the front stage to eliminate the current harmonics, increase the input power factor and keep the dc bus voltage at a constant voltage against line voltage and load current variations.…”
Section: Introductionmentioning
confidence: 99%